Young suicidal people – their emotional characteristics - Gawda, B. (Psychological Prospects Journal, 2012)
The aim of this article is to present the emotional characteristics of young suicidal people expressed in the farewell letters. Psychological analysis of these messages let better understanding of their emotions and feelings, their perception of the world, people and themselves. The symptoms of presuicidal syndrome could be expressed in these letters. According to the narrative conceptions, the analysis of farewell letters' form and content is possible. Narrative psychology proposes the techniques of study of the formal, lexical or syntactic aspects of the texts. The main result of presented emotional characteristics expressed in last letters is a great diversity of emotional states; sadness could take the different shades. These results could be useful in the diagnosis of emotional states and prophylaxis.